015 Clinical utility of T1 mapping in cardiac ATTR amyloidosis – diagnostic performance and prognostic capability. (3rd April 2017) - Norrington, K; Martinez-Naharro, A; Kotecha, T; Francis, R; Hutt, DF; Rezk, T; Quarta, C; Treibel, TA; Whelan, CJ; Knight, D; Kellman, P; Ruberg, FL; et al.
Abstract : Objectives: Cardiac failure caused by transthyretin amyloidosis (ATTR) is an underdiagnosed clinical entity which has an important overlapping clinical phenotype with hypertrophic cardiomyopathy (HCM). Native myocardial T1 mapping by CMR is useful for diagnosis in cardiac amyloidosis. Here, we investigate the diagnostic and prognostic value of T1 mapping in the largest ATTR population studied so far as well as patients with HCM. We aimed to: 1) assess the ability of native T1 to diagnose cardiac amyloidosis; 2) compare native T1 to extracellular volume (ECV), and; 3) stratify prognosis. Methods: 134 wild-type ATTR (ATTRwt) (122 males, age 76±7 years), 95 mutant-type (ATTRm) (64 males, age 66±12 years) and 12 mutation carriers (4 males, age 46±8 years) were compared to 44 HCM patients. All subjects underwent CMR with standard SSFP-cine imaging, T1 mapping and ECV measurement. ATTR patients underwent 99m Tc-DPD scintigraphy, the current diagnostic imaging reference standard for ATTR, with uptake determined by semi-quantitative score. Results: Native T1 and ECV were elevated in ATTR compared to HCM (p<0.001) (mean T1: in ATTRwt 1091±52 ms, in ATTRm 1084±68 ms, in HCM 1026±64 ms; mean ECV: in ATTRwt 0.6±0.1, in ATTRm 0.58±0.2 ms, in HCM 0.38±0.1 ms). No significant difference between native T1 and ECV was found between ATTRwt and ATTRm. Native T1 and ECV diagnostic performance was similar for ATTRwt and ATTRm (vs HCM: T1 AUC 0.89; ECV AUC 0.93; p=0.11 for the significance of the difference between areas under the ROC curves). During follow-up, 63 deaths occurred: 34 ATTRwt, 29 ATTRm. Whilst native T1 was not predictive of death, ECV was (HR, 1.130; 95% confidence interval, 1.06–1.2; p<0.001) and remained independent after adjustment for age, N-terminal pro b-type natriuretic peptide, left ventricular (LV) ejection fraction, E/E', LV mass index, global longitudinal strain and tricuspid annular plane systolic excursion. Conclusions: CMR-determined native myocardial T1 and ECV provide excellent diagnostic accuracy for identification of ATTR cardiac amyloidosis and both variables track DPD-determined amyloid burden well. In this study, whilst T1 was not a predictor of mortality, ECV was independently associated with mortality.